2010
DOI: 10.1159/000313745
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndromes: An Executive Summary from the Consensus Conference of the Acute Dialysis Quality Initiative (ADQI)

Abstract: The cardiorenal syndrome (CRS) is a disorder of the heart and kidneys whereby acute or chronic dysfunction in one organ may induce acute or chronic dysfunction of the other. The general definition has been expanded into five subtypes reflecting the primacy of organ dysfunction and the time-frame of the syndrome: CRS type 1 = acute worsening of heart function leading to kidney injury and/or dysfunction; CRS type 2 = chronic abnormalities in heart function leading to kidney injury or dysfunction; CRS type 3 = ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 79 publications
2
78
0
11
Order By: Relevance
“…Discussion of prevention and management are beyond the scope of this review. [54][55][56] Acute Cardio-Renal syndrome (Type 1 CRS) Type I CRS is characterized by an acute heart disorder leading to AKI. The incidence of AKI in acute decompensated heart failure and acute coronary syndrome is estimated to be 24-45% and 9-19%, respectively.…”
Section: Syndromes Of Acute Kidney Injurymentioning
confidence: 99%
“…Discussion of prevention and management are beyond the scope of this review. [54][55][56] Acute Cardio-Renal syndrome (Type 1 CRS) Type I CRS is characterized by an acute heart disorder leading to AKI. The incidence of AKI in acute decompensated heart failure and acute coronary syndrome is estimated to be 24-45% and 9-19%, respectively.…”
Section: Syndromes Of Acute Kidney Injurymentioning
confidence: 99%
“…20 Increasing evidence has revealed that the intrarenal renin-angiotensin system (RAS) plays a vital role in maintaining hemodynamic balance and cardiorenal interaction, which are often disrupted in patients with acute heart failure. 21,22 In animal studies, activation of the intrarenal RAS is an initial response to hypoperfusion in cardiac and renal injury, and is also an important contributor to the progression of the disease.…”
mentioning
confidence: 99%
“…A precipitating event usually contributes to the development of CRS type 5 in a chronic patient, for example, a spontaneous bacterial peritonitis in a patient with cirrhosis. Therefore, we may find superimposition of acute CRS type 5 on an indolent chronic process with immediate relevance for intensive care physicians, nephrologists, and cardiologists [51].…”
Section: Chronic Kidney Disease -From Pathophysiology To Clinical Impmentioning
confidence: 99%